Ways to develop digital competence of business entities: https://doi.org/10.5281/zenodo.13833633 - Saidahmedova, Dilafruz; Abdiyeva, Dilsuz (Science technology&Digital finance, 2024)
This article is devoted to the development of digital competence of business entities in Uzbekistan. The article scientifically substantiates the need to develop digital entrepreneurship in modern conditions, as well as the content, essence of the concept of digital competence and ways of its development.